Exploring the Manifestations of English Speaking Anxiety in a Drama Performances - Salsabila Balqis; Suciana Wijirahayu (Universitas Islam Negeri Palopo, 2026)
This study investigates students’ speaking anxiety in drama-based speaking tasks in an English as a Foreign Language (EFL) classroom, focusing on its multidimensional manifestations and impact on performance. Using a convergent parallel mixed-methods design, data were collected from eleventh-grade students through questionnaires, classroom observations, and semi-structured interviews. The findings reveal that speaking anxiety manifests across emotional, cognitive, physical, and behavioral dimensions, with cognitive anxiety being the most dominant. Students frequently experienced memory lapses, loss of concentration, and reduced fluency during performance. In addition, anxiety persisted after the performance, particularly during video reflection. These findings indicate that while drama activities can enhance engagement, they may also intensify performance-related anxiety. Therefore, it is important for teachers to implement supportive strategies that address both cognitive and emotional aspects of anxiety to improve students’ speaking performance.